Hábitos alimenticios y su incidencia en la desnutrición crónica en menores de 5 años que acuden al centro de salud Barreiro, Babahoyo, Provincia Los Ríos. Segundo semestre 2017 - Jiménez Baquerizo, Tanya Brigith (2018)
The present investigation had the question of knowing the Alimentary Habits and their Incidence in the Chronic Malnutrition in children under 5 years that go to the Barreiro Health Center, Babahoyo, and Los Ríos Province. Second Semester 2017. Which states that having a healthy diet during childhood is essential for proper growth and development both physical and mental, making it known that the stage where you acquire eating habits is fundamental in childhood and are perfected in adolescence, by which is important to maintain a balanced diet to avoid problems of malnutrition due to excess or deficit in the future, directly affecting the school and interpersonal performance of the boy and girl. A methodology is used that responds to the demands of the research by building a scientific knowledge through a bibliography obtained from various sources, in addition, a data sheet is taken where weight-height is evaluated according to the age to perform the respective analysis based on in the development parameters of the boy and girl. The investigation is carried out in the place of the facts with a direct contact with the involved ones, verifying and interpreting the results obtained to be able to establish the alimentary habits in the children so it is adopted with a nutritional guide for mothers of family.